Impact of Ferritin Level Among Blood Donors at the Central Blood Bank in Tripoli (Comprehensive Journal of Science, 2025)
This cross-sectional study employed a purpose-designed questionnaire, along with laboratorytests, to assess ferritin levels among 20 male donors (aged 20-51 years) at Tripoli’s CentralBlood Bank. The questionnaire collected data on demographics, medical history, irondeficiency-related symptoms, and knowledge of the risks associated with frequent blooddonation. Results revealed that 45% of participants reported symptoms such as fatigue anddizziness, while 15% showed iron deficiency (ferritin ≤30 ng/mL), particularly among regulardonors. Despite 75% being aware of the risks of iron depletion, none had undergone predonation iron testing. The study highlights the value of combining questionnaires withlaboratory screening to identify at-risk donors and recommends enhanced donor educationand routine ferritin testing to mitigate iron deficiency in blood donors.
Keywords: Iron deficiency, Blood donors, Ferritin, Frequent donation